New high-throughput measurement systems for radioactive wastes segregation and free release - Suran, J; Kovar, P; Smoldasova, J; Solc, J; Skala, L; Arnold, D; Jerome, S; de Felice, P; Pedersen, B; Bogucarska, T; Tzika, F; van Ammel, R (Applied radiation and isotopes, 2017)
This paper addresses the measurement facilities for pre-selection of waste materials prior to measurement for repository acceptance or possible free release (segregation measurement system); and free release (free release measurement system), based on a single standardized concept characterized by unique, patented lead-free shielding. The key objective is to improve the throughput, accuracy, reliability, modularity and mobility of segregation and free-release measurement. This will result in a more reliable decision-making with regard to the safe release and disposal of radioactive wastes into the environment and, resulting in positive economic outcomes. The research was carried out within "Metrology for Decommissioning Nuclear Facilities" (MetroDecom) project.
Keywords: Free release; Nuclear decommissioning; Radioactive waste; Clearance level